Almond Breeding: important issues and challenges for research - Dicenta F.; Egea J.; Ortega E.; Martínez-Gómez P.; Sánchez-Pérez R.; Rubio M.; Martínez-García P.J.; Gómez E.M.; del Cueto J.; Sánchez-Prudencio A.; Cremades T. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Due to the recent sharp increase in prices, the almond has become a very profitable culture. This has changed the landscape, not only for the productive sector, but also for breeders that have to satisfy the new demands of nurseries, growers, industry and consumers. The traditional goals of almond breeding in the Mediterranean basin, like late flowering and self-compatibility, currently allow the profitable almond cultivation in cold areas. The new extra-late flowering cultivars are allowing its cultivation in extremely cold areas, in which almonds had never been cultivated. In these areas, early maturation will be an essential trait of new cultivars. In this new environment, resistance to pests and diseases will be a new challenge for breeders, to reduce production costs, develop an agriculture friendly with the environment and produce healthier almonds. Due to the huge demand of almonds, the prices of different cultivars have approached and so, productivity will be the main trait over any other characteristic. However, almond quality will be a significant commitment in the future by designing cultivars for each industrial use. Although modern irrigated plantations, as Californian or Australian, are being imposed in many areas, in the Mediterranean basin there are thousands of rainfed hectares, for which we will have to bred suitable cultivars and rootstocks, and apply appropriate techniques of cultivation. Biotechnological advances will be very useful, facilitating breeders’ efforts by means of Marker Assisted Selection (MAS) for the main characteristics (flowering time, self-compatibility, bitter taste) or molecular identification of cultivars. Breeders have the responsibility to obtain new good cultivars, which must be seriously evaluated in different growing areas and culture conditions before offering them to nurseries and growers.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)